Toxic epidermal necrolysis (scalded skin syndrome) with special reference to contact with kerosene resulting in a clinically similar condition - Say, Burhan; Usubütün, Erdoğan (The Turkish Journal of Pediatrics, 1963)
The authors present three cases diagnosed as toxic epidermal necrolysis and discuss the early use of steroid therapy in the treatment of this disease. Three additional cases are reported in which the patients suffered exposure to kerosene prior to developing symptoms which closely resembled toxic epidermal necrolysis.